2007
DOI: 10.1152/ajpgi.00331.2006
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the murine intestinal alkaline phosphatase geneAkp3impairs lipid transcytosis and induces visceral fat accumulation and hepatic steatosis

Abstract: Intestinal alkaline phosphatase (IAP) is involved in the process of fat absorption, a conclusion confirmed by an altered lipid transport and a faster body weight gain from 10 to 30 wk in both male and female mice with a homozygous null mutation of the IAP coding gene ( Akp3−/− mice). This study was aimed to delineate morphologically and quantitatively the accelerated lipid absorption in male Akp3−/− mice. Feeding a corn oil bolus produced an earlier peak of triacylglycerol in serum (2 vs. 4 h for Akp3−/− and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
69
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 39 publications
(57 reference statements)
1
69
1
Order By: Relevance
“…Moreover, fatty meals increase the levels of IAP in serum and lymph (15,35). Mice homozygous for Akp3 null mutation showed faster body weight gain when fed a high-fat diet, as well as an increased lipid clearance, after a single oral administration of corn oil (38,40). Together, these findings indicate that IAP is involved in regulating enterocyte lipid absorption in the intestinal mucosa.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Moreover, fatty meals increase the levels of IAP in serum and lymph (15,35). Mice homozygous for Akp3 null mutation showed faster body weight gain when fed a high-fat diet, as well as an increased lipid clearance, after a single oral administration of corn oil (38,40). Together, these findings indicate that IAP is involved in regulating enterocyte lipid absorption in the intestinal mucosa.…”
Section: Discussionmentioning
confidence: 85%
“…This suggests that intestine-specific Pdx1 inactivation may have an effect on enterocyte differentiation and that this effect may be more profound in some stem cells/crypts than the others, given that IAP is a common marker of enterocyte differentiation and maturation. Of note, Nakano et al (38) reported that the duodenum of Akp3 Ϫ/Ϫ null mutant mice shows considerable residual alkaline phosphatase activity, and subsequently, Narisawa et al (39) …”
Section: E G and I)mentioning
confidence: 99%
“…Its location suggests an involvement in the uptake of nutrients, but its role has not yet been defined. A relationship with the process of fat absorption (4) and preservation of the normal homeostasis of the gut microbiota has been described previously (5) . IAP expression parallels that of other intestinal proteins involved in Ca absorption under vitamin D stimulation: Ca channel TRPV6, calbindin CD 9k , calcium sodium exchanger NCX 1 and Ca pump PMCAb1 (3,6,7) .…”
mentioning
confidence: 94%
“…In fact, wild-type mice fed a high-fat diet, or challenged with an oil bolus by oral gavage, are commonly reported as having no lipid droplet (LD) accumulation in enterocytes (9)(10)(11). Nevertheless, both indirect and direct evidence exists supporting the presence of a cytoplasmic storage pool in enterocytes.…”
mentioning
confidence: 99%